Delineation of Nubian sandstone aquifer using geophysical data around Nuweiba area, Sinai, Egypt - S. A. S. Araffa; H. S. Sabet; M. H. Mahmoud (Applied Water Science, 2023)
Abstract The Nubian sandstone aquifer (NSA) is defined by using 19 vertical electrical sounding (VES) stations, 201 gravity stations, which define the structures that control the configuration of the NSA, and 183 land magnetic stations, which define the lower surface of the NSA by determining the depth of the basement surface. In order to assess the top of the NSA, we collected and analyzed 19 deep VESes. The upper surface depth of the NSA spans from 707 to 1154 m, according to the interpretation results for various geophysical data. Additionally, the aquifer’s resistivities ranged from 30.2 to 477 Ω m, which indicates good groundwater quality. According to the interpretation of the gravity result, the study region is influenced by many structural characteristics of different trends, including northwest–southeast, northeast–southwest, and east–west trends. The upper surface depth of crystalline rocks (also known as basement rocks) is determined by three-dimensional magnetic modeling to range between 967 and 4122 m.